(untitled) (Global Journal of Science Frontier Research, 2017)
An avian bird community in a forest was classified in to guilds apriori with the objective of determining whether species in the community are clustered naturally in response to bottom processes that have significant direct and indirect effects on birds at various levels of ecological organization. The Harena forest had five habitat categories resulted from spatial variations in collective abundance construct of woody plant species. The constraining effect of this division of the forest in habitat quality was the bird community there was found to have 9 guilds classified according to their adaptive traits which resulted in their matching niche occupancy in the forest with segregations as determined apriori. The number of habitat types occupied by the 9 guilds reflected or was equivalent to the number of habitat types determined from the collective abundance construct of woody plant species.